A mixed-methods study of driver education informed by the Goals for Driver Education: Do young drivers and educators agree on what was taught?. (October 2018) - Rodwell, David; Hawkins, Alana; Haworth, Narelle; Larue, Grégoire S.; Bates, Lyndel; Filtness, Ashleigh
Highlights: Goals for Driver Education (GDE) used to evaluate a novice driver education course. Perceptions of young drivers and driver educators is compared and contrasted. Misalignment in perceptions about what the driver education course focused on. Novice drivers perceive training is more related to concrete influences on driving. Indication that driver educators may tend to combine particular components of GDE. Abstract: Evaluation research suggests that professional driver education and training has little effect on reducing the crash involvements of young drivers. Driver education and training programs have been criticised as being unsystematically designed and lacking an empirical or theoretical basis. The Goals for Driver Education (GDE) is a theoretical framework developed to address these criticisms. The GDE defines four hierarchical levels of driving behaviours and influences on driving and three individualised Person-specific factors that should be considered in driver education and training programs. The aim of this study was to compare and contrast, in a methodologically rigorous manner, the perceptions that young drivers ( n  = 22; Mage = 17.80 years, SD  = 6.54 months) and driver educators ( n  = 10; Mage = 54.5 years, SD  = 9.21 years) have of a professional driver education and training course they participated in or facilitated. Eight semi-structured focus groups were conducted and the GDE was used to direct the collection and analysis of the data. Young drivers mainly discussed basic driving skills located on the lower levels of the GDE rather than higher level abstract factors that increase risk for young drivers. Driver educators tended to group particular GDE levels and Person-specific factors together when discussing the driving course and paid limited attention to Goals and contexts of driving. Results suggest that driver educators should provide direct instruction regarding the more abstract social and contextual factors that influence driving to potentially increase the efficacy of driver education and training as a safety countermeasure.